(untitled) (Journal of the College of Basic Education, 2025)
In the paper focuses on the synthesis and characterization of Schiff bases using 1,2,4-triazole and graphene oxide (rGO) compounds, along with their applications. Specifically, it explores the conversion of graphene-to-graphene oxide and reduced graphene oxide (RGO) and their reactions with thiocarbhydrazone. The study shows how to prepare Schiff bases from different aldehydes and thiocarbhydrazides and then combine them with RGO that has been modified with sulfadiazine to make nanocomposites. These synthesized compounds were investigated for structural properties using infrared spectroscopy, X-ray diffraction, and FESEM imaging. In addition, the antibacterial activity of the resulting materials was evaluated, showing significant bacterial inhibition, especially against E. coli, with varying efficacy depending on the concentration of the material.